2022
DOI: 10.3390/photonics9050349
|View full text |Cite
|
Sign up to set email alerts
|

The BER Performance of the LDPC-Coded MPPM over Turbulence UWOC Channels

Abstract: Turbulence-induced fading is a critical performance degrading factor for underwater wireless optical communication (UWOC) systems. In this paper, we propose a quasi-cyclic (QC) low-density parity-check (LDPC) code with multiple-pulse-position modulation (MPPM) to overcome turbulence-induced fading. MPPM is adopted as a compromise between the low-power efficiency of on–off keying (OOK) and the low bandwidth efficiency of pulse position modulation (PPM). The bit error rate (BER) performance of LDPC-coded MPPM ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…It is vital to prioritize modulation schemes with high transmission rates or high transmission efficiency while assuring dependability [ 21 , 22 , 23 ]. Most UWOC studies have been carried out utilizing PPM, or on-off keying (OOK), as the modulation format in the water channel.…”
Section: Resultsmentioning
confidence: 99%
“…It is vital to prioritize modulation schemes with high transmission rates or high transmission efficiency while assuring dependability [ 21 , 22 , 23 ]. Most UWOC studies have been carried out utilizing PPM, or on-off keying (OOK), as the modulation format in the water channel.…”
Section: Resultsmentioning
confidence: 99%
“…They hold promise for underwater inspection and exploration due to their sufficient bandwidth, reliability, and cost-effectiveness. In 2022 [15], authors proposed a quasi-cyclic low-density parity-checked (QC-LDPC) code with multiple-pulse-position modulation (MPPM) to address turbulenceinduced fading in UWOC systems. MPPM offers a balance between power and bandwidth efficiency.…”
Section: Related Workmentioning
confidence: 99%
“…After investigating and comparing BER performance of different modulation systems, including OOK, PPM and MPPM, it was found that the UWOC performs better when applying LDPC code and MPPM instead of other modulation schemes. LPDC was also verified to be efficient in improving communication system with much better BER performance compared with BER performance of uncoded systems [7].…”
Section: Introductionmentioning
confidence: 96%